Non-Marxian Historical Materialism: Reconstructions and Comparisons - Brzechczyn, Krzysztof (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2022)
The authors of this book reconstruct the philosophical, methodological and theoretical assumptions of non-Marxian historical materialism, a theory of historical process authored by Leszek Nowak (1943-2009), a co-founder of the Poznań School of Methodology. In the first part of the book, philosophical assumptions of this theory are compared with the concepts of Robert Nozick, Immanuel Wallerstein, André Gunder Frank and analytical Marxism. In the second part, non-Marxian historical materialism is compared with the concepts of Eva Etzioni-Halevy, Andrzej Falkiewicz, Robert Michels, Vilfredo Pareto, Theda Skocpol and Karl August Wittfogel.